1994
DOI: 10.1007/bf00327771
|View full text |Cite
|
Sign up to set email alerts
|

Immunologicalization of complement C1s and matrix metalloproteinase 9 (92kDa gelatinase/type IV collagenase) in the primary ossification center of the human femur

Abstract: The first component of complement C1s has been shown to degrade type I and type II collagens (Yamaguchi et al. 1990), the latter of which is a major constituent of the cartilage matrix. In order to understand the physiological roles of C1s in cartilage resorption, the expression of C1s was examined by immunohistochemistry in the primary ossification center where the matrix is removed and replaced by bone marrow. Hypertrophic chondrocytes, endothelium and hematogenous elements in the capillary buds were intense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The initiating enzyme of the classical pathway, C1s, has been localized to hypertrophic chondrocytes within the primary ossification center of the femur, and its collagen-degrading activity has been linked to matrix degradation during endochondral bone formation [77]. Primary osteoblasts secrete C3 in response to 1α,2,5-dihydroxyvitamin D 3 , and C3 also appears to synergistically promote M-CSF-dependent osteoclast differentiation from bone marrow progenitors [78].…”
Section: Complement In Mammalian Regenerative Processesmentioning
confidence: 99%
“…The initiating enzyme of the classical pathway, C1s, has been localized to hypertrophic chondrocytes within the primary ossification center of the femur, and its collagen-degrading activity has been linked to matrix degradation during endochondral bone formation [77]. Primary osteoblasts secrete C3 in response to 1α,2,5-dihydroxyvitamin D 3 , and C3 also appears to synergistically promote M-CSF-dependent osteoclast differentiation from bone marrow progenitors [78].…”
Section: Complement In Mammalian Regenerative Processesmentioning
confidence: 99%
“…Recent studies were able to provide first evidence for an involvement of complement in bone biology [1921]. …”
Section: Discussionmentioning
confidence: 99%
“…C1s possesses the ability to degrade Type 1 and 2 collagen [44]. Immunohistochemical analysis of the primary ossification center of the human femur revealed that C1s co-localizes with MMP-9 throughout this region, including hypertrophic chondrocytes, mesenchymal cells and the extracellular matrix [44].…”
Section: The Complement Cascade and Cellular Growth And Regenerationmentioning
confidence: 99%
“…Immunohistochemical analysis of the primary ossification center of the human femur revealed that C1s co-localizes with MMP-9 throughout this region, including hypertrophic chondrocytes, mesenchymal cells and the extracellular matrix [44]. C1s can also cleave the zymogen of MMP-9 and activate its protease activity [44]. Their co-localization implies a coordinated role in the turnover of cartilage to bone [44].…”
Section: The Complement Cascade and Cellular Growth And Regenerationmentioning
confidence: 99%